STRATEGI PEMBELAJARAN INOVATIF BERBASIS TEKNOLOGI DIGITAL: Pendekatan Adaptif dan Diferensial - Zainal Falah; Syahlarriyadi; Anna Ropitasari (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
This study aims to design an innovative learning strategy based on digital technology that integrates adaptive and differential approaches to meet the diverse learning needs of students. With a qualitative-descriptive research design, this study was conducted at Madrasah Tsanawiyah Assa'adah Ulujami which has adopted digital technology. Data were collected through observation, in-depth interviews, and documentation, then analyzed using a thematic analysis approach. The results of the study indicate that the integration of digital technology, such as an artificial intelligence-based Learning Management System (LMS), online collaboration tools, and gamification elements, can significantly improve the quality of learning. The adaptive approach allows personalization of materials based on student abilities, while the differential approach supports a variety of methods to meet diverse learning needs. The findings also revealed obstacles in the form of limited infrastructure and internet access, which are obstacles to the optimal implementation of this technology. This study concludes that digital technology-based learning strategies not only increase the effectiveness of learning but also strengthen the inclusiveness of education. Policy recommendations include the development of technological infrastructure, teacher training, and expansion of research to test the effectiveness of strategies on a wider scale.